2018
DOI: 10.6000/1929-4409.2018.07.01
|View full text |Cite
|
Sign up to set email alerts
|

Working Behind Bars: Employed Prisoners' Perception of Professional Training and Employment in Prison

Abstract: The research is aimed at examining the perceptions and attitudes of prisoners employed in enterprises in prison vis-à-vis employment and deriving conclusions regarding the impact of employment on the lives of prisoners in prison and its contribution to advancing their rehabilitation. Doing time is generally a painful experience, both physically and mentally, and often adversely influences prisoners' life after release. Programs and activities have been developed in prisons in many countries, including Israel, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 36 publications
(41 reference statements)
1
3
0
Order By: Relevance
“…Prisoners staffing the restaurants were no longer considered as inmates but rather as trainee hospitality employees capable of delivering outstanding service, which further highlights the potential success of vocational training in reducing reoffending (Cale et al, 2018). This also supports the findings by Peled-Laskov and Timor (2018) who concluded that the opportunity for employment alongside gaining soft skills positively contributes to prisoners' self-image, self-respect and confidence.…”
Section: Discussionsupporting
confidence: 60%
See 3 more Smart Citations
“…Prisoners staffing the restaurants were no longer considered as inmates but rather as trainee hospitality employees capable of delivering outstanding service, which further highlights the potential success of vocational training in reducing reoffending (Cale et al, 2018). This also supports the findings by Peled-Laskov and Timor (2018) who concluded that the opportunity for employment alongside gaining soft skills positively contributes to prisoners' self-image, self-respect and confidence.…”
Section: Discussionsupporting
confidence: 60%
“…Working there equips them with catering and life skills and allows them the opportunity to engage with the general public as an opportunity to gain confidence before release and integration back into society. The benefits of interaction with the public before release is a finding echoed in previous research (see Peled-Laskov and Timor, 2018). Therefore, the restaurants not only prepare them for the life outside with the help of the mentoring programme but also give them a taste of that life whilst still inside the prison.…”
Section: Prison: the Inside And Outside Dividementioning
confidence: 67%
See 2 more Smart Citations